Meningkatkan Hasil Belajar Peserta Didik tentang Perhitungan Multidays Tour dengan Menggunakan Metode Tutor Sebaya - Dede Suryana (Transformasi Manageria: Journal of Islamic Education Management, 2022)
This research departs from the phenomena that occur in the classroom that the students' understanding and learning outcomes are low in learning Multidays Tour Calculation in the Subjects of Travel Planning and Management. Therefore, an educator needs to consider learning strategies so that they can improve student learning outcomes. This study aims: (1) To find out that Peer Tutor learning methods can improve student learning outcomes about Multidays Tour Calculations in Travel Planning and Management Subjects in class XII UPW 2 Semester 1 SMK Negeri 1 Bogor Bogor City for the 2019/2020 academic year, (2) To describe the process of improving student learning outcomes before and after using Peer Tutor learning methods can improve student learning outcomes about Multidays Tour Calculations in the Subject of Travel Planning and Management in class XII UPW 2 Semester 1 SMK Negeri 1 Bogor Bogor City Academic Year 2019/2020, (3) To measure the increase in student learning outcomes regarding Multidays Tour Calculations in the Subject of Travel Planning and Management after using the Peer Tutor Learning Method in class XII UPW 2 Semester 1 SMK Negeri 1 Bogor Bogor City Academic Year 2019/2020. The results of this study indicate that applying the Peer Tutor Learning Method can be a fun variation of learning for students so that it is proven to improve student learning outcomes in Class XII UPW 2 SMK Negeri 1 Bogor, Bogor City. Before applying the Peer Tutor Learning Method, the students' learning outcomes only reached an average value of 69.97, then there was an increase after applying the Peer Tutor Learning Method to 75 in cycle 1 and 84 in cycle 2. From the description above, the researcher concludes that the application of the Peer Tutor Learning Method that is adapted to the learning material can create a pleasant learning situation so that there is an increase in student learning outcomes. Therefore, the researcher suggests that the application of the Peer Tutor Learning Method be socialized and used as an alternative in learning Travel Planning and Management in schools within the Bogor City Education Office. Keywords: Peer tutor learning methods, student learning outcomes, Travel Planning and Management subjects